BICO MPPT: A Faster Maximum Power Point Tracker and Its Application for Photovoltaic Panels - Hadi Malek; YangQuan Chen (International Journal of Photoenergy)
This paper develops a maximum power point tracking (MPPT) algorithm to optimize photovoltaic (PV) array performance and make it more compatible to rapidly varying weather conditions. In particular, a novel extremum seeking controller (ESC), which uses a Bode ideal cutoff (BICO) filter in its structure, is designed and tested on a simulated PV array. The new algorithm is compared against the commonly used ESC MPPT algorithm with first-order filters. The BICO extremum seeking controller achieves transient rise to the MPP faster than the common extremum seeking MPPT, which is the faster and more robust method among all other methods. This claim has been discussed and proved mathematically in this paper, in addition to simulation illustrations. This faster extremum seeking algorithm enables PV systems to detect rapid variations in the environmental conditions like irradiation and temperature changes.